The Perceived Broad Group Emotional Climate Scale: Development and Validation With Chinese Community Residents and University Students - Yang, Xiao-juan; Wang, Xin-qiang; Liu, Jian-ping; Lai, Song-hai; Liu, Mingfan; Ye, Baojuan (Frontiers in Psychology, 2021)
Perceived broad group emotional climate (PBGEC) is a perceived meso-environment emotion, which refers to individuals’ perceptions and experiences of the emotion climate when interacting with group members in daily life, and is not derived from individuals’ own emotions. The purpose of this study was to develop and validate a PBGEC scale (PBGECS) for Chinese community residents and university students. A total of 1,408 residents from Chongqing completed the survey of PBGECS, the present social attitude scale, the future social expectations scale, and the social wellbeing scale, which constituted Sample 1; A total of 607 college students from Nanchang completed the survey of PBGECS and the Positive and Negative Affect Scale, which constituted Sample 2. Exploratory factor analysis revealed a two-factor structure, including positive PBGEC (PBGEC-P) and negative PBGEC (PBGEC-N). Internal consistency was strong for each factor and the full-scale (α ≥ 0.83). Confirmatory factor analysis showed that the correlated two-factor model of PBGEC and the four-factor model (including PBGEC-P, PBGEC-N, individual positive affect, and individual negative affect) demonstrated the best fit to the data, which supported the structural validity of the PBGECS. The interpretive validity, cultural validity, and population validity of the scale were also proved by examining the relationship between PBGEC and socioeconomic status, social attitude, and social wellbeing, respectively. The results show that the PBGECS demonstrated satisfactory reliability and validity, which can be used to assesses the perceived emotion climate of an individual’s surrounding environment.